Long-term changes in Black-browed albatrosses diet as a result of fisheries expansion: an isotopic approach - Mariano y Jelicich, Rocío (2017)
Ecological changes due to fishing activities appear to be similar across marine ecosystems; in this context the application of retrospective studies could help understand the magnitude of such impact on apex predators. Carbon and nitrogen stable isotopic values of feathers were used to evaluate if the observed expansion in Argentine fisheries operating in the Patagonian Continental Shelf affected Black-browed albatrosses (BBAs) diet. Feather samples from museum skins and from contemporary birds captured at sea were compared. Samples from the “pre-expansion” period showed enriched carbon values compared to recent samples. No differences in δ15N were observed between periods, suggesting that if a diet change occurred it did not affect trophic levels exploited by BBAs. Isotopic niche width of contemporary BBAs was wider than the one for historic albatrosses suggesting, for the former, a more variable diet. Given that cephalopods from the Patagonian Continental Shelf showed enriched carbon values compared to pelagic and demersal prey, our results suggest a trend from a cephalopod-based diet during the pre-fisheries expansion period towards a demersal prey-based diet in a contemporary fishing context. Despite the limitations imposed by retrospective studies, our results show that a shift in the diet of the Black-browed albatross in waters of the Patagonian Continental Shelf could have occurred as a result of ecosystem changes promoted by the expansion of industrial fisheries and mostly through the emergence of discards as an abundant and predictable food source.